Optimisation and Application of Biorenewable Polymers - Jacob, Philippa L. (2024)
Unsustainable polymer production over decades has resulted in significant amounts of environmentally accumulative, fossil-fuel derived polymers. One approach to obtaining more sustainably sourced polymers, is through the conversion of bioderived monomers from industrial by-products into new polymers. In this thesis, two molecules, β-pinene and glycerol, both derived from industrial by-products, have been exploited in the production of more sustainable polymers. Herein, for the first time, poly(β-pinene) has been prepared via cationic polymerisation using iron-based Lewis acid ionic liquid (LA-IL) catalysts with good conversion and with Mn up to 2000 g mol-1. A small library of LA-ILs were screened and it was found that LA-ILs could be considered a greener alternative to the more conventionally used Lewis acids in cationic polymerisation. FeCl3, an earth-abundant, cost-effective catalyst has been used in an industrially optimised scale up of the cationic polymerisation. Finally, purification of the polymer using scCO2 extraction was found to efficiently remove unreacted monomer and solvent with potential for recycling in the future. The post-polymerisation functionalisation of poly(β-pinene) yielded polymeric surfactants capable of self-assembly and oil/water emulsion stabilisation. Partial hydrogenation of poly(β-pinene) resulted in an almost two-fold increase in oxidative stability. The synthesis of glycerol-based polymers derived from poly(glycerol adipate), incorporating new chemical handles and hydrophobic moieties into the polymer backbone has also been investigated. The polymer modification was achieved by replacing 50% of the glycerol with another diol. A range of functionalities have been introduced into the polymer backbone, avoiding the use of multi-step reactions usually required in polymer modifications. The self-assembling properties, as well as the ability of the polymer nanoparticles to encapsulate small molecules were shown to be significantly influenced by the incorporation of the new functionalities. Further work investigated the replacement of glycerol with diglycerol, a more hydrophilic polyol. Although poly(diglycerol adipate) did not form stable nanoaggregates, its modification with 1,6-n-hexanediol resulted in stable nanoaggregates with good encapsulation properties.